Revisiting debates of premature luteinization and its effect on assisted reproductive technology outcome - Hussein, Reda S. (J Assist Reprod Genet, 2019)
The impact of the prematurely elevated serum progesterone on the late follicular phase, commonly known as premature luteinization (PL), is a matter of continuing debate. Available evidence supports that serum progesterone ≥ 1.5 ng/ml on the day of ovulation triggering could reduce the pregnancy potential in fresh in vitro fertilization (IVF) cycles by jeopardizing endometrial receptivity. Causes of PL during ovarian stimulation are unclear. Recent studies point toward the daily follicle-stimulating hormone dosage, duration of controlled ovarian stimulation, number of oocytes retrieved, and peak estradiol level as factors affecting the incidence of PL. Emerging data show additional influence on embryo quality. The prevention of PL has been challenging. The key elements in preventing PL include individualization of ovarian stimulation according to patient’s ovarian reserve, proper ovulation trigger timing, and use of medications such as corticosteroids and metformin. Embryo cryopreservation with deferred embryo transfer is the established strategy to overcome PL, yet it is an extra burden to the IVF laboratory and increased cost for patients. Herein, we review the up-to-date knowledge of this frequent IVF problem including causes, proposed diagnostic criteria, and its impact on endometrial receptivity, embryo quality, and pregnancy outcomes. The preventive measures and rescue strategies are also discussed.